Analysis of thrips (Thysanoptera: Thripidae) diversity in avocado shows the presence of a new species and limitations of using the COI gene for differentiation of two species - Cano-Calle, Daniela; Saldamando-Benjumea, Clara Inés; Moreno-Herrera, Claudia Ximena; Arango-Isaza, Rafael Eduardo (Revista Colombiana de Entomología, 2021)
Thrips are important pests of avocados causing damage to the fruits, making them unsuitable for exportation. Many of them are quarantine species and their identification is necessary. Despite their importance, not many studies describe thrips diversity on avocado, especially in Colombia, partly because identification of some of the species is difficult using classical taxonomic keys. In this study, 93 adult thrips specimens were collected on avocado and adventitious dandelion plants from plantations in the department of Antioquia, Colombia. Morphological characters were used to classify 62 of them and all of them were analyzed by PCR amplification and sequencing of cytochrome c oxidase subunit I (COI) gene and internal transcribed spacer (ITS) region. The species identified by morphological features were Frankliniella gardeniae Moulton, F. gossypiana Hood, F. panamensis Hood, Liothrips perseae Watson, Thrips palmi Karny, T. simplex (Morison), T. trehernei Priesner, Microcephalothrips abdominalis (Crawford DL), and Scirtothrips hansoni Mound & Hoddle (Tubulifera), being F. panamensis, M. abdominalis, and S. hansoni reported for the first time on avocado in Colombia. Thrips simplex and T. trehernei were also found on adventitious dandelion plants, but not on avocado. Phylogenetic analysis of COI and ITS sequences showed that most species, except for F. gardeniae and F. gossypiana were mainly identified with the COI gene. Furthermore, FST values obtained between them suggest no genetic differentiation at COI level. The results obtained here contribute to the knowledge of the diversity of thrips species found on the avocado crop in Colombia and are meaningful for pest management.